2018
DOI: 10.1002/jcb.27668
|View full text |Cite
|
Sign up to set email alerts
|

Total flavonoids from Smilax glabra Roxb blocks epithelial‐mesenchymal transition and inhibits renal interstitial fibrosis by targeting miR‐21/PTEN signaling

Abstract: Background: Smilax glabra Roxb, a traditional Chinese herb, has been widely used in folk medicine. The current study was performed to investigate the protective effect of S. glabra Roxb extract, pure total flavonoids from Smilax glabra Roxb (PTFS), on renal interstitial fibrosis (RIF) and its underlying mechanism.Methods: First, a surgical model of unilateral ureteral obstruction was established in rats to induce RIF. Then, rats were grouped and treated with PTFS at different concentration. Second, HK-2 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
2
16
1
Order By: Relevance
“…Gain-and loss-offunction studies revealed that miR-21 positively regulated BEV-induced EMT by decreasing the expression of E-cadherin and increasing the expression of α-SMA. Many researches about the relationship of miR-21 and EMT in other tissues[21][22][23]32] are consistent with our results, which further prove our conclusion. However, miR-21-5p were downregulated in TGFβ2-induced EMT in human RPE cells[31].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Gain-and loss-offunction studies revealed that miR-21 positively regulated BEV-induced EMT by decreasing the expression of E-cadherin and increasing the expression of α-SMA. Many researches about the relationship of miR-21 and EMT in other tissues[21][22][23]32] are consistent with our results, which further prove our conclusion. However, miR-21-5p were downregulated in TGFβ2-induced EMT in human RPE cells[31].…”
supporting
confidence: 91%
“…Usui-Ouchi A et al found that upregulation of miR-21 levels in the vitreous humor is associated with development of proliferative vitreoretinal disease by promoted cell proliferation and migration in RPE cells [20]. Many studies in other organs have shown that miR-21 is involved in the EMT of cells [21][22][23][24]. Snail is a zincfinger transcription factor and one of the best-known functions of Snail is to regulate EMT during tumorigenesis and fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…3A). Studies have revealed that PTEN is the negatively regulated target of miR-21 (31,32). Western blot analysis revealed that the miR-21 mimic led to a significant downregulation of PTEN expression, whereas the miR-21 inhibitor led to a significant upregulation of PTEN expression ( Fig.…”
Section: Geniposide Inhibits Apoptosis Induced By Ox-ldl Inmentioning
confidence: 94%
“…The main compounds in S. glabra extract are flavonoids; the content is ~687 mg rutin equivalents/g dry extract. Pure total flavonoids from S. glabra Roxb have affects against renal fibrosis and epithelial-mesenchymal transition in vitro and in vivo ( Luo et al., 2019 ). The n-butyl alcohol fraction of S. glabra extract has been shown to inhibit the swelling rate of paws and levels of IL-1β, IL-6 and TNF-α in carrageenan-induced arthritic rats ( Bao et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%